Optimization of administration and monitoring of prevention of venous thrombosis and inflammatory wound complications. - Bereznytskyi, Ya. S.; Ksikevich, L. N. (Medicni Perspektivi, 2018)
Modern surgery and anesthesiology make it possible to perform complex surgical interventions, but at the same time, there are postoperative complications that, on the one hand, worsen the quality of surgical care provided and increase the cost of its implementation, and on the other hand do not exclude the possibility of fatal cases in operated patients. The aim of the work is the development, of on the principles of information technology process of selecting algorithms for the justified administration of preventive measures for the prevention of thrombosis and wound complications in surgical patients. We have developed and implemented the process of selecting preventive measures at the pre-operative stage, including them into the electronic list of medical administrations, the practical use of planned actions in a hospital environment, monitoring the timeliness and scope of their implementation, with further support of these algorithms and taking into account the results achieved as a result of their application. The developed process of administering standardized algorithms for prophylaxis of thromboembolic and wound complications with control of their performance is effective and practically meaningful.